Dual Risk Guarantee Mechanism for Net-Zero City Financing in Indonesia - Rifky Pratama Wicaksono; Muhammad Rafi Bakri (Journal of Infrastructure Policy and Management, 2026)
The development of Net-Zero Cities (NZCs) in Indonesia faces significant obstacles due to complex financing mechanisms and inherent governance challenges in Public-Private Partnerships (PPPs). Although PPPs have become a strategic instrument for addressing the financing gap in green infrastructure, high fiscal risks, uncertain benefits, and weak intergovernmental coordination continue to hinder their effectiveness. In this context, PT Penjaminan Infrastruktur Indonesia (PT PII) plays a vital role in mitigating risks by providing government-backed guarantees for infrastructure PPPs. However, the effectiveness of this role depends on oversight mechanisms conducted by the Audit Board of Indonesia (BPK) as the state audit institution. This paper therefore introduces the concept of a dual risk guarantee mechanism, which combines PT PII’s infrastructure guarantees with BPK’s fiscal oversight. Through this scheme, the feasibility of NZC projects can be strengthened, fiscal risks can be more carefully monitored, and public investment governance can be improved. The study draws on document analysis and case-based studies of contemporary practices in Indonesia. The authors find that the acceleration of NZCs requires robust oversight, the establishment of contingency funding, optimization of gearing ratios, risk transparency, and stronger synergy of PT PII, BPK, the Ministry of Finance, and other stakeholders.